In vitro cultivation of Trypanosoma congolense bloodstream forms in the absence of feeder cell layers - Hirumi, H.; Hirumi, K. (Cambridge University Press, 1991)
Bloodstream forms ofTrypanosoma congolense(2 clones: ILNat3·1 and IL3000, and 4 stocks: IL2079, IL2466, IL3266 and CP-81) were continuously cultivatedin vitroat 34–36 °C in the absence of feeder cell layers, using HMI-93 medium which was modified from Iscove's modified Dulbecco's MEM (Flow Laboratories, Irvine, Scotland). The modification was done by supplementing the medium with 0·05 mM bathocuproine sulphonate, 1·5 mM L-cysteine, 0·5 mM hypoxanthine, 0·12 mM 2-mercaptoethanol, 1 mM sodium pyruvate, 0·16 mM thymidine, 20% (v/v) heat-inactivated young goat serum and 5% (v/v) Serum Plus™ (Hazleton Biologics, Lenaxa, KS, USA). Trypanosomes obtained from two different sources were used to initiate primary cultures: (1) metacyclic forms which were producedin vitroat 27 °C, and (2) bloodstream forms obtained from Balb/c mice which had been infected with the bloodstream forms transformedin vitrofrom the metacyclic forms. Metacyclic forms placed in 25 cm2T-type (T-25) flasks rapidly attached to the bottom of the flasks and transformed to bloodstream forms during the initial 24 h and continued to proliferate. The bloodstream forms isolated from the infected mouse blood by means of diethylaminoethyl cellulose (DE52) column chromatography also continued to proliferate in the flasks. Cultures were maintained by replacing the medium every 24 h. Every 4–5 days, the attached bloodstream forms were resuspended in fresh medium by gentle pipetting and then were subcultured. The method was further simplified by initiating primary cultures directly with 10 μl of the tail blood of infected mice in 24-well culture plates and then by subcultivating either in wells or in T-25 flasks. The shortest population doubling time, 9 h, was achieved by seeding subcultures with 106bloodstream forms/ml. The bloodstream forms propagated in this system were morphologically similar to those seen in infected mouse blood, they were covered with a surface coat as examined by electron microscopy and they were infective to mice.